Detection of human retrovirus 5 in patients with arthritis and systemic lupus erythematosus. - Griffiths, D; Cooke, S; Hervé, C; Rigby, S; Mallon, E; Hajeer, A; Lock, M; Emery, V; Taylor, P; Pantelidis, P; Bunker, C; du Bois, R; et al. (1999)
OBJECTIVE: To examine whether human retrovirus 5 (HRV-5) infection is associated with autoimmune rheumatic disease. METHODS: DNA from patients with various disorders including inflammatory diseases and from normal subjects was tested by nested polymerase chain reaction (PCR) for HRV-5 proviral DNA. Positive results were confirmed by DNA sequencing. RESULTS: HRV-5 proviral DNA was detected in 53% of synovial samples from arthritic joints, in 12% of blood samples from patients with rheumatoid arthritis (RA), and in 16% of blood samples from patients with systemic lupus erythematosus. In contrast, it was not detectable by PCR of affected tissues from patients with several other autoimmune diseases and was found in only 1 of >200 tissue specimens obtained at autopsy from non-RA patients. Sequence analysis of the amplified viral segment showed genetic variation between samples with maintenance of the open reading frame, typical of a replicating infectious retrovirus. CONCLUSION: This is the first report of the frequent detection of HRV-5 in any disease. We propose that the possible involvement of HRV-5 in autoimmune and rheumatic disease should be investigated further.